Harnessing Technology to Enhance Teacher Competency and Improve Learning Quality in Schools - Rifa'i, Moh; Koironi, Weliya Alifn Robeth (Journal of Educational Management Research, 2025)
This study aims to explore technology interventions in educational environments, focusing on technology adaptation as a critical case study. This study highlights how institutions with limited resources can design innovative strategies for integrating technology into learning. This study uses a qualitative approach with a comprehensive research design. Data were collected through in-depth interviews, participant observation, and document analysis with 15 key informants, comprising school leaders, educators, and students. Triangulation techniques were used to ensure data validity. The results showed that, despite facing infrastructure limitations, successful adaptive strategies were implemented, including a projector rotation system and a hybrid learning model. This strategy increased student engagement by 35% and reduced teacher preparation time by around 20%. The application of technology to focus on productive subjects enables the visualisation of complex concepts more effectively, strengthens student understanding, and bridges theory and practice. This study confirms that digital transformation in education relies not only on technological infrastructure but also on educators’ creative capacity to redesign pedagogical approaches. This study offers a conceptual framework for effective technology integration in resource-constrained educational settings, providing a novel contribution to the literature on constraint-based digital learning innovation.